Descobrindo a geometria esférica com Anselmo - Silva, Henrique José Cavalcante Chagas da (2024)
This dissertation proposes an interdisciplinary analysis between the narrative of the comic book The Adventures of Anselmo Curioso - The Mysteries of Geometry written by the French scientist Jean-Pierre Petit, and the fundamental concepts of spherical geometry. The aim is to make this complex area accessible to advanced high school students and undergraduates in the field of exact sciences. Spherical geometry is explored through the adventures experienced by the character Anselmo, providing a playful and contextualized approach to understanding concepts such as geodesics, triangles, and angles on a spherical surface. The comic book narrative is broken down into scenarios that connect to specific aspects of spherical geometry. Through a meticulous analysis of Anselmo Curioso’s adventures, parallels with geometric definitions are identified, illustrating abstract concepts through practical situations present in the stories. Concrete examples are presented, such as the shortest distance between New York and Madrid, highlighting how the interaction of the characters and events in the comic book reflects and symbolizes aspects of spherical geometry, making the underlying mathematical principles more tangible. We conclude that the relationship between Anselmo’s adventure and the principles of spherical geometry offers a valuable opportunity to demystify advanced mathematical concepts, encouraging interest and deeper understanding of these topics among students.